Effect of Low-Intensity Endurance Training and High-Intensity Interval Training on Sperm Quality in Male Rats with Fatty Liver - Hosseini, Mahnaz (Int J Fertil Steril, 2021)
BACKGROUND: We aimed to investigate the effect of low-intensity endurance training (LIET) and high-intensity inter- val training (HIIT) on sperm parameters, chromatin status, and oxidative stress in a rat model of non-alcoholic fatty liver disease (NAFLD). MATERIALS AND METHODS: For this experimental study, we divided 40 male Wistar rats into four groups (control, sham, HIIT and LIET) according to diet treatment and exercise training protocol. Liver triglycerides, sperm parameters, sperm lipid peroxidation (BODIPY C11 probe) and chromatin status [chromomycin A3 (CMA3)], and acridine orange [AO] staining) were assessed in these groups at the end of the study. RESULTS: The mean liver triglyceride values significantly improved in both the LIET and HIIT groups compared to the control and sham groups. The mean of testicular volume, sperm concentration, motility, intensity of sperm lipid peroxidation and DNA damage were similar within groups. While, the mean percentage of sperm lipid peroxidation and protamine deficiency were significantly higher in the LIET and HIIT groups compared to the control group. CONCLUSION: Both LIET and HIIT in the rat NAFLD model had no adverse effects on testicular morphometric param- eters, sperm concentration, motility, and DNA integrity. However, the mean sperm lipid peroxidation and protamine deficiency were significantly higher in both exercise groups. Our study suggests that exercise or antioxidant supple- mentation could minimise the adverse effects of oxidant by-products of exercise.